Inhaled Antibiotics for the Prevention of Respiratory Tract Infections in Children With a Tracheostomy - Jutras, Camille; Autmizguine, Julie; Chomton, Maryline; Marquis, Christopher; Nguyen, The Thanh-Diem; Roumeliotis, Nadia; Emeriaud, Guillaume (Frontiers in Pediatrics, 2021)
Objective: To describe the use of prophylactic inhaled antibiotics in children with a tracheostomy and assess if its use is associated with a reduction to broad-spectrum antibiotics and a lower risk of acquired respiratory tract infections. Methods: A case series study was performed in a tertiary care university affiliated hospital. All consecutive children (<18 years old) with a tracheostomy, hospitalized between January 2004 and November 2016, and treated with prophylactic inhaled antibiotics were identified. We analysed the 3 month- period before and after initiation of prophylactic inhaled antibiotics and described exposure to broad spectrum antibiotics, the number of respiratory tract infections and the associated adverse events. Results: Six children (median age: 11 months, range: 8-100) were included. One received colimycin, 3 received tobramycin and 2 were treated with both antibiotics in alternance. The median duration of treatment was 74 days (22-173) with one patient still being treated at the end of the study. Patients were exposed to systemic antibiotics for 18 days (2-49) in the 3 months preceding the treatment versus 2 days (0-15) in the 3 months following the treatment initiation (p=0.115). The number of respiratory tract infections went from median of 2 (0-3) to 1 (0-1) during the same periods (p=0.07). Adverse events most commonly reported were cough (n=2) and increased respiratory secretions post-inhalation (n=4). Only one new bacterial resistance was observed. Conclusions: This series of consecutive cases underlines the need for future studies evaluating the potential benefit of prophylactic inhaled antibiotics in children with a tracheostomy.